ANALYSIS OF BARRIERS IN LISTENING COMPREHENSION AMONG JUNIOR HIGH SCHOOL STUDENTS - Setia Muljanto (University of Kuningan, 2012)
Abstract: This research paper identifies barriers and difficulties in listening comprehension faced by junior high school students. The research questions were what barriers did students encounter and how did they used strategies to overcome those barriers. This study used a qualitative method and was a case study involving 40 students and one English teacher. The data were obtained by ways of conducting a test of listening taken from TOEIC test. The tests indicated that the results scores were not quite satisfactory. This is primarily caused by speech delivery of the native speaker which was too fast. This means that students faced listening barriers especially in processing information. The data also indicated that students were also nervous when doing the test as habitual barrier. Strategies used to overcome these barriers are by making students get used to listen and use English and making them familiar with certain contexts in real life. Â Keywords: listening barriers, listening comprehension, TOEIC test.